Low-Dose Aspirin In The Prevention Of Pre-Eclampsia With Potential Bleeding Risk Undergoing Treatment In Tertiary Care Hospital - Upasana, Mishra (Journal of Neonatal Surgery, 2025)
The present research is assessing the potential of low-dose aspirin as a preventative measure for pre-eclampsia. The incidence of postpartum hemorrhage (PPH) did not change statistically significantly between the aspirin and control groups. The purpose of this study was to assess the possible bleeding risk of 100 mg aspirin in high-risk pregnant women (62) as well as the variation in PPH incidence based on maternal factors. At five follow-up visits, coagulation test results and platelet counts were gathered. The study examined subgroups based on mother age (less than 35 years and more than 35 years), pre-pregnancy body mass index (pre-BMI, less than 28 kg/m² and more than 28 kg/m²), parity, gestational age at enrolment, and medical history, which included diabetes mellitus, chronic hypertension, and pre-eclampsia. To determine if there was a significant difference in the incidence of PPH following aspirin administration to pregnant women in each subgroup, logistic regression analysis was employed. Multiple logistic regression models were used to make changes after these findings. The aspirin and control groups did not vary significantly in terms of bleeding risk . When examining certain subgroups, there was no discernible difference in the overall incidence of PPH between the aspirin group and the control group. There was no significant correlation between pre-BMI and PPH in the control group, but there was in the aspirin group. Regardless of the mother's characteristics, a daily dose of 100 mg of aspirin, starting between weeks 12 and 20 and continuing until weeks 34, did not raise the risk of possible bleeding and PPH. There was a substantial positive connection between PPH and BMI in the aspirin group.